2001
DOI: 10.1021/jf0110699
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and Accumulation of Shikimic Acid in Response to Glyphosate Applications in Glyphosate-Resistant and Nonglyphosate-Resistant Cotton (Gossypium hirsutum L.)

Abstract: Measurement of shikimic acid accumulation in response to glyphosate inhibition of 5-enolpyruvylshikimate-3-phosphate synthase is a rapid and accurate assay to quantify glyphosate-induced damage in sensitive plants. Two methods of assaying shikimic acid, a spectrophotometric and a high-performance liquid chromatography (HPLC) method, were compared for their accuracy of recovering known amounts of shikimic acid spiked into plant samples. The HPLC method recovered essentially 100% of shikimic acid as compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
115
1
10

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(137 citation statements)
references
References 20 publications
(30 reference statements)
8
115
1
10
Order By: Relevance
“…Singh & Shaner (1998) and Mueller et al (2003) reported recoveries higher than 80% of spiked shikimic acid in crude extracts of soybean, maize and horseweed. Recoveries of 100% of shikimic acid in spiked samples of cotton, and 85% to 104% in fortified wheat tissue were also reported by Pline et al (2002) and Anderson et al (2001), respectively.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Singh & Shaner (1998) and Mueller et al (2003) reported recoveries higher than 80% of spiked shikimic acid in crude extracts of soybean, maize and horseweed. Recoveries of 100% of shikimic acid in spiked samples of cotton, and 85% to 104% in fortified wheat tissue were also reported by Pline et al (2002) and Anderson et al (2001), respectively.…”
Section: Resultssupporting
confidence: 65%
“…This herbicide acts by inhibiting the enzyme 5 -e n o l p y r u v y l s h i k i m a t e -3 -p h o s p h a t e synthase (EPSPS), thereby causing rapid and high levels of shikimic acid to accumulate in affected plant tissues . Measurement of shikimic acid accumulation in response to glyphosate inhibition is a rapid and accurate way to quantify and predict glyphosate-induced damage in sensitive plants (Harring et al, 1998;Pline et al, 2002;Henry et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matallo et al (2009), trabalhando com glyphosate e concentração de ácido chiquímico em citros, observaram que as plantas que receberam aplicação de glyphosate mostraram sempre maiores concentrações de ácido chiquímico que as plantas testemunhas. Vá-rios pesquisadores (Singh & Shaner, 1998;Wang, 2001;Mueller et al, 2003) (Mueller et al, 2003;Koger et al, 2005), algodão (Pline et al, 2002), girassol, trigo e milheto (Henry et al, 2007), soja (Singh & Shaner 1998) e trigo (Bresnahan et al, 2003.…”
Section: Resultsunclassified
“…Pline et al (2002) examinaram o acúmulo de ácido chiquímico em variedades de algodão tanto sensíveis como resistentes ao glyphosate e também constataram aumento na concentração de ácido chiquímico nas folhas de algodão transgênico, sendo esse aumento muito inferior ao conteúdo encontrado nos frutos. Segundo esses autores, provavelmente esse aumento pode ser devido a uma menor demanda dos produtos da via do ácido chiquímico nas folhas.…”
Section: Resultsunclassified